Reflections from Occupational Therapies from the South: Structural Violence, Human Rights and Gender in Processes of Accompaniment of Women During Pregnancy and Mothering [Reflexiones Desde Las Terapias Ocupacionales Desde el Sur: Violencia Estructural, Derechos Humanos y Género en Procesos de Acompañamiento de Mujeres Durante el Embarazo y maternaje1 - Diaz-Diaz, M; Palomino-Araneda, T (Universidade Federal de Sao Carlos, 2021)
It is a report of experiences that arises from an ongoing investigation that characterizes the intervention model of an Intensive Outpatient Program of treatment for drug and/or alcohol consumption specific for adult women in pregnancy or puerperium at Hospital El Pino, in Santiago de Chile. The objective is to advance some reflections based on this ongoing research experience, focusing on the forms of accompaniment that the team of occupational therapists carries out in these programs. The antecedents, theoretical elements that guide this research, the procedures, and the reflections on the accompaniment processes carried out by the occupational therapy team are presented, considering the preliminary qualitative analyzes. The first research actions around this experience show us that the accompaniment processes in occupational therapy located from decolonial perspectives, allow a political-theoretical reading based on human rights and gender, making visible the structural violence produced by the colonial system/modern/patriarchal/racial running through the life stories of women and their families. It is essential to guarantee the rights of women, to articulate actions in the spaces of daily life, and to strengthen the various support and support networks for the reconstruction of their life projects. It is concluded that drug use, the experience of pregnancy, and mothering are conditioned by the inequalities, stigmatization, and structural violence of the modern colonial system, which is why it is very relevant that the accompaniments in occupational therapy incorporate decolonial perspectives from the south. © 2021 Universidade Federal de Sao Carlos. All rights reserved.